2014
DOI: 10.1373/clinchem.2013.219956
|View full text |Cite
|
Sign up to set email alerts
|

Validation of DNA Methylation Biomarkers for Diagnosis of Acute Lymphoblastic Leukemia

Abstract: BACKGROUND DNA methylation biomarkers capable of diagnosis and subtyping have been found for many cancers. Fifteen such markers have previously been identified for pediatric acute lymphoblastic leukemia (ALL). Validation of these markers is necessary to assess their clinical utility for molecular diagnostics. Substantial efficiencies could be achieved with these DNA methylation markers for disease tracking with potential to replace patient-specific genetic testing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Not surprisingly, large-scale analyses of epigenetic phenomena have shown clear correlations between epigenetic patterns and patient outcome. Correlations between DNA methylation and clinical prognosis have been observed for many cancers, including glioblastoma, acute myeloid leukemia (AML), 6 T-cell and B-cell lymphoblastic leukemia, lung carcinoma, ovarian carcinoma, and melanoma (516). …”
mentioning
confidence: 99%
“…Not surprisingly, large-scale analyses of epigenetic phenomena have shown clear correlations between epigenetic patterns and patient outcome. Correlations between DNA methylation and clinical prognosis have been observed for many cancers, including glioblastoma, acute myeloid leukemia (AML), 6 T-cell and B-cell lymphoblastic leukemia, lung carcinoma, ovarian carcinoma, and melanoma (516). …”
mentioning
confidence: 99%
“…Biomarkers of minimal residual disease in pediatric acute lymphoblastic leukemia [35] Colorectal cancer DNA methylation…”
Section: Tlx3 Foxe3mentioning
confidence: 99%
“…DIAGNOSTIC AND PROGNOSTIC EPIGENETIC APPROACHES Indeed, DNA methylation biomarkers capable of diagnosis and subtyping have been investigated in several hematopoietic tumors as well as prognostic ones [33]. A validation study of some of these markers led to a reliable detection of DNA methylation of the TLX3 and FOXE3 genes, which allowed the monitoring of minimal residual disease in pediatric ALL patients [35]. For instance, in a genome-wide association study on pediatric acute lymphoblastic leukemia (ALL) 325 genes were found to be hypermethylated and downregulated and 45 genes hypomethylated and upregulated [34].…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…Genetic alterations include the mutation of the protein-coding region or loss of heterozygosity (LOH) and microsatellite instability (MSI) in the coding or non-coding regions. Epigenetic changes typically involve the methylation of promoter DNA or histone acetylation (7).…”
Section: Introductionmentioning
confidence: 99%
“…MSI is the polymorphism in the length of these microsatellite sequences; they may affect amino acid codons or the regulation of transcription (8). At present, various MSI phenotypes have been identified in a number of tumor types (7,8). The mechanism of inactivating mutations and deletions of both alleles of a tumor suppressor gene was involved in the process of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%